The Clinicopathological and Prognostic Value of PD-L1 Expression in Cholangiocarcinoma: A Meta-Analysis - Xu, Gang; Sun, Lejia; Li, Yunzhu; Xie, Feihu; Zhou, Xiaoxiang; Yang, Huayu; Du, Shunda; Xu, Haifeng; Mao, Yilei (Frontiers in Oncology, 2019)
Abstract 1. Background: Recently, immune checkpoint blockade has emerged as one of the most potential treatments for solid tumors. Programmed cell death ligand 1(PD-L1), a member of the B7 family of molecules, plays a crucial role in tumor immunobiology. However, the prognostic significance of PD-L1 in cholangiocarcinoma (CCA) patients remains controversial. The objective of this study was to inquire into the prognostic and clinicopathological significance of PD-L1 in CCA via a meta-analysis. 2. Methods: We searched PubMed, Embase, the Cochrane Library, Web of Science and Google Scholar up to April 2019, regardless of the region or language, for studies on the correlation between prognosis or clinicopathology and PD-L1 in patients with CCA. The pooled hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated to investigate the prognostic significance of PD-L1 expression in cholangiocarcinoma. The odds ratios (ORs) were also calculated to explore the association between PD-L1 expression and clinicopathological features. 3. Results: Eleven studies including 1,066 patients were included in our meta-analysis. The meta-analysis of these studies showed a trend that high PD-L1 expression indicated a poor OS, but the result was not statistically significant (HR=1.62, 95% CI[0.98-2.68], p=0.063). For DFS, although the pooled result is not statistically significant, it trends toward being significant that high PD-L1 expression indicated improved DFS (HR=0.80, 95% CI[0.62, 1.04], p =0.092). In subgroup analyses, the results were not consistent across the subgroups that were divided based on the publication year (before 2018: HR=1.92, 95% CI[1.34-2.75], p< 0.001; after 2018: HR=1.42, 95% CI[0.70-2.89], p=0.335). Moreover, PD-L1 expression in TCs was significantly correlated with the AJCC TNM stage of CCA (OR=0.52, 95% CI[0.27, 0.99], p=0.09). 4. Conclusion Our meta-analyses revealed that PD-L1 expressed in TCs was significantly correlated with the AJCC TNM stage of CCA. Based on the included studies, we found that PD-L1 indeed expressed in both TCs and ICs in CCA patients, raising the possibility of the use of anti-PD-1/PD-L1 therapy for CCA patients. In contrast, expression of PD-L1 did not seem to be associated with patient outcome in our study. The prognostic role of PD-L1 in CCA demands further investigation.